Social indicators and other income statistics using EUROMOD: An assessment of the 2001 baseline and changes 1998 - 2001 - Christine Lietz; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2005)
This paper reports an exercise to validate EUROMOD output for 2001 by comparing income statistics calculated from the baseline micro-output with comparable statistics from the European Community Household Panel (ECHP). It focuses particularly on some of the income-based common “Laeken” social indicators. It also compares EUROMOD estimates of changes in these indicators between 1998 and 2001 with similar estimates based on ECHP. The values of many of the indicators – and changes to the indicators – calculated using EUROMOD are close to those shown by the ECHP. Where there are discrepancies these can usually be explained by known differences in the methods or underlying data. Users of EUROMOD should be aware of remaining unavoidable sources of non-comparability across countries, as well as the nature of the simulation process. Nevertheless they can be confident that the baseline provides a good starting point for the analysis of the effects of policy changes on indicators.
Keywords: C81; D31; I32; 330; European Union; Microsimulation; Poverty statistics; Income inequality